Strategi Komparatif Iklan Televisi Produk Shampoo Wanita - Herry P, Basnendar (Institut Seni Indoensia Surakarta, 2009)
The advertisement is an important element in culture because it reflects and attempts to change our life style. Advertisment does not only offer commodity, but it also offers sexuality, beauty, facilitation, modernity, happiness, success, and status. Talking about television advertisement through cultural perpective is an unfailing topic to discuss because it is related to the broad and crucial question. The advertisement intens to give stimulation to the target audience in order to create buying and selling condition. So does television advertisement to reach a wider target, it will be more effective to the advertisers if they use this media. The research takes the category of body treatment advertised in television electronic media. The advertisement of shampoo products to be compared in this research are : Pantene Pro-V Shampoo advertisement and CLEAR Shampoo advertisement, where both advertisement contain comparative stategy. The research finds that the three advertisements of the shampoo product, the comparative of the way to use the product, and the comparative from the product itself so it can be categorized that comparative strategy from both shampoo products burn into monotonous and tend to be clichÃ©.Keyword : television advertisement, comparative strategy, shampoo product